(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic changed the routine of Brazilians, generating direct impacts on their eating habits. Objective: To analyze the implications of the COVID-19 pandemic on the eating habits of Brazilians, based on the scientific production published in 2020. Methodology: Study of an integrative literature review, whose search for articles was carried out on the Virtual Health Library portal, in December 2020, using the descriptors in English: food, eating habits, food consumption, COVID-19, Coronavirus infections. Publications of original articles, with a quantitative or qualitative approach, carried out in Brazil between April and November 2020 were included. The data extracted were: title, author, year, journal, objectives, methodology, population / sample, results and conclusions of each study. Results: The dietary changes resulting from the pandemic differed depending on the age group and the individual’s socioeconomic and health conditions. In most of the analyzed articles, negative impacts were observed, with emphasis on the increase in the consumption of ultra-processed foods and reduction in the consumption of vegetables, especially in adults with depression, individuals with lower income and education. The consumption of unhealthy foods has often been combined with a sedentary lifestyle, representing risky behaviors for the development of chronic diseases. However, some studies have shown positive changes in the eating habits of adults, with a slight increase in the consumption of healthy eating markers, and a reduction in the consumption of fast foods by adolescents. Final considerations: Long-term studies are needed to better understand the impacts of the COVID-19 pandemic on eating habits, as well as to guide actions to fight the disease and the consequences of this worldwide phenomenon on the health of brazilians.